Pembatalan Pengangkatan Anak Pasca-Baligh dalam Perspektif Maslahah Mursalah dan Hukum Positif: Analisis Putusan Pengadilan Negeri Nganjuk Nomor 31/Pdt.G/2022/PN Njk: Anak angkat - Eka Yunita, Eka Yunita Rahmawati; Hidayat, Eko; Novalia, Sisca (Kartika: Jurnal Studi Keislaman, 2026)
The annulment of child adoption after the child reaches adulthood raises legal issues at the intersection of legal certainty, child protection, and individual autonomy. This study aims to analyze the legitimacy of such annulment under Indonesian positive law and to assess its conformity with the principle of maslahah mursalah. The analysis focuses on the Decision of the Nganjuk District Court Number 31/Pdt.G/2022/PN Njk. This research employs a normative legal method with statutory, case, and conceptual approaches. The findings indicate that, within the framework of positive law, the annulment of child adoption is legally permissible as long as it is conducted through a valid judicial mechanism and based on the principle of the best interests of the child, particularly after the child attains full legal capacity. However, the decision also reflects a shift from a legal certainty approach toward a welfare-based approach, which may lead to legal uncertainty in the absence of clear parameters. From the perspective of maslahah mursalah, such annulment does not contradict the principle of lineage preservation (ḥifẓ al-nasl) and can be justified insofar as it promotes genuine benefit and prevents harm. This study underscores the need for more comprehensive regulatory frameworks to ensure a balance between legal certainty, public benefit, and the protection of children's rights within Indonesia’s family law system